Tinjauan Al Qur'an dalam Term Kecerdasan Intelektual - Hamzani Aulia Rahman; Abdul Hafiz Alfatoni (PALAPA, 2021)
The Qur'an is the first source of Islam in the guidelines of Islamic life. In each verse and letter there is a meaning to seek a deep search of all implied objects. Therefore one of the potentials of man in taking a knowledge is reason. Reason becomes an intelligence in building human civilization in the future, reason is also able to guard and nurture man in all his ugliness and error. Therefore it is necessary as a Muslim to have an intellectual in understanding many things. In the Intellectual Qur'an there is a lot of influence on the meaning of attachment to every meaning contained in each verse of the holy book, one of which is the word Nazara (obsevasi) which is depicted in the letter at-Thariq, tafakkara (thinking) in sura al-Baqarah, and Fahima (understanding) al-Anbiya'. Then in all its interpretations using the tool of the ancient knife only believe to be used as a belief and some who research it with all its flaws, so that in this century a lot of authenticity and truth in the holy book of the Koran to be used as a source of knowledge to be associated in the current research both in terms of intellectual, emotional and spiritual.